The Juridical Act as a historiography category - Irti, Natalino (2016)
This article addresses the issue of the pre-legal nature of the Juridical and its stratification in the social and legal level. Also, it contrasts the theory of the will and the theory of the declaration, and refers to the controversy between Emilio Betti and Giuseppe Stolfi about the dispute over the language. The idea of monism is developed in the theory of the Juridical Act quoting Santi Romano and Hans Kelsen, as well as its tensions with dualism. Finally, it takes Juridical Act as historiographical category, and its relationship to the problems of technological society and closes with the gap between private autonomy and Juridical Act.